Tracheostomy in paediatric patients - Saraf, Aditiya; Begh, Raies Ahmad; Jyoti, Deep; Jamwal, Padam Singh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The objective of the study was to evaluate paediatric tracheostomies in the Department of ENT, GMC. Methods: The present prospective study was performed in the Department of ENT, GMC Jammu from January 2018 to 2020 on 20 paediatric patients (<17 years of age). All children were evaluated with respect to age, indication of tracheostomy, complications (intra-operative and post-operative) and mortality. Results: The most common indication for tracheostomy was prolonged intubation (85%). Intraoperative complication in the form of creation of false passage was seen in 1 patient (5%). The most common early post-operative complication was tube obstruction (20%). Late complication in the form of stomal granulation was seen in 2 patients (10%). Conclusions: Over the years, more specific indications for tracheostomy are followed and better results are observed. Paediatric tracheostomy at our institute was associated with less procedure related morbidity and mortality.